2010
DOI: 10.1016/j.arr.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure and aging

Abstract: The study of energy expenditure (EE) has deep roots in understanding aging and lifespan in all species. In humans, total EE decreases substantially in advanced age resulting from parallel changes in resting metabolic rate (RMR) and activity EE. For RMR, this reduction appears to be due to a reduction in organ mass and specific metabolic rates of individual tissues. However, these anatomical changes explain very little regarding the decline in activity EE, which is governed by both genetic and environmental sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(164 citation statements)
references
References 116 publications
(133 reference statements)
5
151
0
8
Order By: Relevance
“…However, it is likely that the activitystat setpoint may be flexible and dynamic; varying for example with season, age or energy intake. It is widely accepted that total energy expenditure [12] and moderate to vigorous physical activity [13][14][15] vary systematically with age and physical activity levels are higher in the warmer months and decline during the colder seasons [16] . Layered on top of this is a large intra-individual variability in daily physical activity levels of approximately 20% [2,17] .…”
Section: Variable Vs Fixed Setpointsmentioning
confidence: 99%
“…However, it is likely that the activitystat setpoint may be flexible and dynamic; varying for example with season, age or energy intake. It is widely accepted that total energy expenditure [12] and moderate to vigorous physical activity [13][14][15] vary systematically with age and physical activity levels are higher in the warmer months and decline during the colder seasons [16] . Layered on top of this is a large intra-individual variability in daily physical activity levels of approximately 20% [2,17] .…”
Section: Variable Vs Fixed Setpointsmentioning
confidence: 99%
“…For example, individuals with higher metabolic rates have higher energy requirements and may have to spend more time foraging for food or be less likely to survive food shortages. High resting metabolic rates have also been linked to decreased longevity (Manini, 2010;Speakman, 2005). In addition, basal metabolic rates (BMRs) are positively correlated to reproduction, such that species with high BMRs often have higher reproductive rates (Hennemann, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] In addition, it has also been suggested that the appearance of these REE changes may depend on gender, adiposity, and lean body mass. 35,40 The study has some limitations. First, it was performed in a single center, and despite the substantial number of IC measurements, only 24 patients completed the five-day follow-up.…”
Section: Discussionmentioning
confidence: 99%